Cerebrospinal Fluid Shunting for Idiopathic Intracranial Hypertension: A Systematic Review, Meta-Analysis, and Implications for a Modern Management Protocol. Issue 4 (4th October 2022) - Salih, Mira; Enriquez-Marulanda, Alejandro; Khorasanizadeh, MirHojjat; Moore, Justin; Prabhu, Vikram C.; Ogilvy, Christopher S.
Abstract : BACKGROUND: Cerebrospinal fluid (CSF) shunting is widely used in refractory idiopathic intracranial hypotension (IIH). Although multiple reviews have assessed its efficacy compared with other surgical treatments, there is no detailed analysis that evaluates the clinical outcomes after CSF shunting. OBJECTIVE: To conduct a meta-analysis of the clinical impact of CSF shunting for refractory IIH and use this in conjunction with existing information on other treatment modalities to develop a modern management protocol. METHODS: PubMed and Embase were systematically searched for studies describing CSF shunting for medically refractory IIH. Relevant information including study characteristics, patient demographics, clinical outcomes, periprocedural complications, and long-term outcomes were subjected to meta-analysis. RESULTS: Fifteen studies published between 1988 and 2019 met our inclusion and exclusion criteria, providing 372 patients for analysis. The mean age was 31.2 years (range 0.5-71) with 83.6% being female. The average follow-up was 33.9 months (range 0-278 months). The overall rate of improvement in headache, papilledema, and visual impairment was 91% (95% CI 84%-97%), 96% (95% CI 85%-100%), and 85% (95% CI 72%-95%), respectively. Of 372 patients, 155 had 436 revisions; the overall revision rate was 42% (95% CI 26%-59%). There was no significant correlation between average follow-up duration and revision rates in studies ( P = .627). Periprocedural low-pressure headaches were noted in 74 patients (20%; 95% CI 11%-32%). CONCLUSION: CSF shunting for IIH is associated with significant improvement in clinical symptoms. Shunting rarely causes periprocedural complications except overdrainage-related low-pressure headache. However, CSF shunting has a relatively high revision rate.